The tumor suppressor gene DAPK2 is induced by the myeloid transcription factors PU.1 and C/EBPα during granulocytic differentiation but repressed by PML‐RARα in APL. Issue 1 (13th September 2013) - Humbert, Magali; Federzoni, Elena A.; Britschgi, Adrian; Schläfli, Anna M.; Valk, Peter J. M.; Kaufmann, Thomas; Haferlach, Torsten; Behre, Gerhard; Simon, Hans‐Uwe; Torbett, Bruce E.; Fey, Martin F.; Tschan, Mario P.
Abstract : Transcriptional mechanisms responsible for low DAPK2 levels in particular AML subtypes. Abstract : DAPK2 is a proapoptotic protein that is mostly expressed in the hematopoietic tissue. A detailed DAPK2 expression analysis in two large AML patient cohorts revealed particularly low DAPK2 mRNA levels in APL. DAPK2 levels were restored in APL patients undergoing ATRA therapy. PML‐RARA is the predominant lesion in APL causing transcriptional repression of genes important for neutrophil differentiation. We found binding of PML‐RARA and PU.1, a myeloid master regulator, to RARA and PU.1 binding sites in the DAPK2 promoter. Ectopic expression of PML‐RARA in non‐APL, as well as knocking down PU.1 in APL cells, resulted in a significant reduction of DAPK2 expression. Restoring DAPK2 expression in PU.1 knockdown APL cells partially rescued neutrophil differentiation, thereby identifying DAPK2 as a relevant PU.1 downstream effector. Moreover, low DAPK2 expression is also associated with C/EBPα‐mutated AML patients, and we found C/EBPα‐dependent regulation of DAPK2 during APL differentiation. In conclusion, we identified first inhibitory mechanisms responsible for the low DAPK2 expression in particular AML subtypes, and the regulation of DAPK2 by two myeloid transcription factors underlines its importance in neutrophil development.